Victimhood as victory: The role of memory politics in the process of de-Europeanisation in East-Central Europe. Issue 1 (29th January 2019) - Vermeersch, Peter
Abstract : To a large extent, the traditional narrative of EU integration has revolved around reconciliation and peace-building after the Second World War. This article examines how current memory work in nationalist movements in East-Central Europe subverts this moral story and uses it as the basis for a politics of backlash against the EU. Recent developments in national commemoration and remembrance practices in the region have enabled not only the glorification of the national past but also the suppression of 'heretical' interpretations of specific traumatic historical episodes. The fault lines of national belonging are now often used to eclipse stories of post-war state reconciliation in Europe and focus directly on the victimised population. As a result, commemorations carry strong normative and moral overtones related to justice and culpability. Nationalism in this context has received moral connotation and, vice versa, questions of morality become questions of nationhood. The 'we' of this distinguishing work embodies a subject of immaculate historical innocence and victimhood; by extension, the 'others' always bear responsibility and guilt. This nationalist moral classification work changes and reframes the moral underpinnings of the EU enlargement. The victim theme has adhered a strong potential to garner solidarity among various social groups in East-Central Europe against the EU. The role of victimiser is easily projected onto both the abstract notion of the 'European elites' and the supposed allies of those elites: the internal 'others'.